MEMPELAJARI KOMUNIKASI ANTARBUDAYA ; Keunikan Individu, Stereotip & Obyektifitas - Wahyu Ardiansyah; abdul Rohim; Lailatul Wahyu Fitriani; suhajis suhajis (Al-Maquro' : Jurnal Komunikasi dan Penyiaran Islam, 2020)
Learning how to be successful in intercultural interaction in the future is important and worth doing. Culture plays an important role in how humans observe and communicate with reality. In a cultural life, we need the same meaning in order to be able to coexist well. Meaning also depends on the stereotype of each individual. There are positive stereotypes and negative ones. That actually a stereotype is an opinion that is drawn without being able to be an exact picture, because our view of the object is more adapted to our background so that later an oddity is born. We must realize that each individual is born with its own uniqueness, so that it does not need to be equated with other individuals especially groups.